2021
DOI: 10.51341/1984-3925_2021v24n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Política de Dividendos e Períodos de Recessão: Evidências no Mercado de Capitais Brasileiro

Abstract: Objective: To observe the dividend distribution behavior of Brazilian stock market [B]³ listed companies, comparing periods of expansion and recession in the Brazilian economy.Method: Two panel data models were carried out, with the payout index and the dividend yield index as dependent variables and a dummy classified as 1 for years of economic recession and 0 for years of economic rise as an independent variable. In addition, the financial leverage, size and earnings per share control variables were added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…In addition to the pandemic period, the present investigation also covered a recession in Brazil, which took place in 2015. The study by Martucheli et al (2021) addressed this topic by comparing the dividend distribution behaviour of companies listed on B3 in periods of expansion and recession in the Brazilian economy. The results showed that, regardless of the distribution of dividends measured by payout or dividend yield, which are also proxies for this work, companies increased the distribution of dividends in periods of recession when there is greater uncertainty in the market.…”
Section: Alternative Leverage (Alev) Presented An Inverse Relationshi...mentioning
confidence: 99%
“…In addition to the pandemic period, the present investigation also covered a recession in Brazil, which took place in 2015. The study by Martucheli et al (2021) addressed this topic by comparing the dividend distribution behaviour of companies listed on B3 in periods of expansion and recession in the Brazilian economy. The results showed that, regardless of the distribution of dividends measured by payout or dividend yield, which are also proxies for this work, companies increased the distribution of dividends in periods of recession when there is greater uncertainty in the market.…”
Section: Alternative Leverage (Alev) Presented An Inverse Relationshi...mentioning
confidence: 99%
“…Given this, it can be inferred that some companies adopt a diligent posture to face the increased selection forces in recessive periods and, beyond the survival of the business, are engaged in adaptations that favor the achievement of resilient performance, as raised throughout the previous section. In this sense, the reconfiguration of internal economic-financial factors that promote return on invested capital occurs and interacts under intui tion that can be illustrated as follows: Most research aiming at understanding business dynamics in periods of economic recession begins by dating the economic cycle (with Codace being the primary source of information in Brazil), a condition that proves sufficient for identifying the exogenous event and applying studies (Carpenter et al, 1994;Opler & Titman, 1994;Hubbard, 1998;Kudlyak & Sánchez, 2017;Brighetti & Albanez, 2019;Martucheli et al, 2021). Therefore, by identifying the business cycle, assimilating the causes and consequences of the recessionary period, and based on the temporal dynamics summarized in Figure 2, it becomes clear that studies related to the determinants of resilient performance during economic crises can be conducted using the following empirical approach.…”
Section: Resilience and Business Cyclesmentioning
confidence: 99%
“…A maioria das pesquisas voltadas à compreensão da dinâmica empresarial em períodos de recessão econômica tem início pela datação do ciclo econômico (sendo o Codace, no Brasil, a principal fonte dessa informação), condição que se mostra suficiente para identificação do evento exógeno e aplicação de estudos (Carpenter et al, 1994;Opler & Titman, 1994;Hubbard, 1998;Kudlyak & Sánchez, 2017;Brighetti & Albanez, 2019;Martucheli et al, 2021). Sendo assim, mediante identificação do ciclo de negócios, assimilação das causas e consequências do período recessivo e a partir da dinâmica temporal resumida na Figura 2, fica notória a possibilidade de os estudos relativos aos determinantes do desempenho resiliente ante período de crise econômica serem conduzidos sobre a estratégia de abordagem empírica indicada na Figura 4.…”
Section: Proposição Para Estratégia De Abordagem Empíricaunclassified